LAND MANAGEMENT, THE MYTH OF DEWI SRI, AND THE BALANCE OF JAVANESE COSMOLOGY, AN ANTHROPOGEOGRAPHIC OVERVIEW - Suwardi Suwardi (Faculty of Geography, Universitas Gadjah Mada, 2013)
The research was conducted in the Prangkokan Village, Purwosari, Girimulyo, Kulon Progo,, Yogyakarta. Thepurpose of this study is to reveal the land management practice in the study area based on the mythl of Dewi Sri who is believed to maintain the balance of cosmos. Significance assessment performed based onanthropogeographic approach. This research was conducted based on qualitative ethnographic methods. Theresults showed that agricultural land management still influenced by the myth of Dewi Sri. This “Dewi Srimyth” is trusted by the farmers because they believe that the gods were able to maintain soil fertility. Dewi Sri myth is also believed to be able to maintain the balance of the cosmos. In anthropogeographic terms, thefarmers live in Prangkokan village are managing arable land and yard with a spiritual mindset. The traditional management of soils apparently is believed can bring fertility and prosperity to the community life.